2019
DOI: 10.1002/hed.25978
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of oral premalignant lesions using a multimodal imaging system: a pilot study

Abstract: Background: Multimodal optical imaging, incorporating reflectance and fluorescence modalities, is a promising tool to detect oral premalignant lesions in real-time. Methods: Images were acquired from 171 sites in 66 patient visits for clinical evaluation of oral lesions. An automated algorithm was used to classify lesions as highor low-risk for neoplasia. Biopsies were acquired at clinically indicated sites and those classified as high-risk by imaging, at the surgeon's discretion. Results: Twenty sites were bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…In clinical practice, histopathology can be complemented by immunochemistry and special stains (e.g., alcian blue and reticulum stain) when the diagnosis cannot solely be made based on histological sections. Currently, new optical technologies are under evaluation combining conventional morphological imaging with molecular imaging (such as specific imaging and metabolic imaging) or multimodal imaging to provide supportive data [43]. Recently, dynamic FFOCT technology has been shown to highlight a low level of backscattered light from structures in the tissue [44].…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, histopathology can be complemented by immunochemistry and special stains (e.g., alcian blue and reticulum stain) when the diagnosis cannot solely be made based on histological sections. Currently, new optical technologies are under evaluation combining conventional morphological imaging with molecular imaging (such as specific imaging and metabolic imaging) or multimodal imaging to provide supportive data [43]. Recently, dynamic FFOCT technology has been shown to highlight a low level of backscattered light from structures in the tissue [44].…”
Section: Discussionmentioning
confidence: 99%
“…Included studies (Table 1) were published between 2006 and 2020, and they were focused on the Autofluorescence technique (n:14) [28][29][30][31][32][33][34][35][36][37][38][39][40][41], HRME (n:5) [42][43][44][45][46], Optical spectroscopy (n:7) [10, [47][48][49][50][51][52], NBI (n:2) [53,54], and Vital Stain Colorants (n:6) [55][56][57][58][59][60]. In total, 34 studies were performed in adults (18 years of age or older).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…According to the Newcastle-Ottawa scale (NOS) on cross-sectional (n:24) [28,29,31,35,37,39,40,[42][43][44][45][46][48][49][50][54][55][56]59,60,[73][74][75][76]; case-control (n:10) [10,32,47,[51][52][53][77][78][79][80] and cohort studies (n:7) [30,34,36,38,41,57,58] the authors evaluated the qualities of all included studies based on object selection, comparability, and exposure. A star was described as an appropriate entry, with each star representing one point.…”
Section: Total Score=mentioning
confidence: 99%
“…[5][6][7][8] Because abnormal nuclear morphology is a key hallmark of oral neoplasia, numerous clinical studies have demonstrated their potential to diagnose oral neoplasia. [9][10][11][12][13][14][15][16] To reduce subjectivity in image interpretation, automated algorithms have been developed to calculate statistical features of nuclei that correlate with neoplasia, like nuclear density, mean nuclear size and variance, nuclear eccentricity, and the nuclear-to-cytoplasm ratio. [17][18][19] These features can then be used as inputs to machine learning algorithms that distinguish neoplastic tissue from benign tissue.…”
Section: Introductionmentioning
confidence: 99%
“… 5 8 Because abnormal nuclear morphology is a key hallmark of oral neoplasia, numerous clinical studies have demonstrated their potential to diagnose oral neoplasia. 9 16 …”
Section: Introductionmentioning
confidence: 99%